(untitled) (Kairaranga, 2016)
Priority learners in New Zealand include those who have special educational needs, yet gifted learners with multiple exceptionalities are variably identified, understood or provided for in our schools. International research advocates the use of interprofessional practice (IPP) teams, with competency across shared values, roles and responsibilities, communication, and teamwork, to support gifted learners with multiple exceptionalities. This study explored the experiences and understandings of IPP teams supporting students with multiple exceptionalities in New Zealand. The study found that IPP team identity is still in its infancy and core competencies are still evolving. Shared values towards inclusive practices were hampered by limited knowledge and expertise across the IPP team. Limited understandings of teamwork processes and limited recognition of the importance of communication within the IPP team were also common themes. Parents and students were typically not recognised as part of the IPP team identity and processes. The article concludes that gifted learners with multiple exceptionalities may not have adequate support at a systems level, and development of interprofessional practice competencies may be one way to ensure their full inclusion in our education system. Implications for policy and practice are described.